THE EFFECT OF CONTROL FOCUS, COURAGE, AND OPEN-MINDEDNESS ON ACADEMIC PERFORMANCE: IMPLICATIONS FOR EDUCATION AND MANAGEMENT - Elsa Sabrina (Perspektif Ilmu Pendidikan, 2023)
Education is pivotal for personal development and societal progress, while management is crucial for resource optimization and goal attainment in organizations. Education shapes individuals, society, while management optimizes resources, goals in organizations. The synergy between education and management is increasingly vital for improving education quality and human resource development. This study explores the relationship between psychological factors (Control Focus, Courage, Open-mindedness) and students' academic performance. In our dynamic world, understanding how these factors impact academic success is crucial. The research aims to guide both education and management sectors. By grasping Control Focus's role in task management, Courage's importance in overcoming challenges, and Open-mindedness's positive effect on innovation and adaptability, collaboration between these fields can be more effective. The conclusions stress the need for closer cooperation between education and management to address complex challenges and achieve success. Additionally, they highlight understanding individual psychology's role in education and organizations, unlocking human potential, and accomplishing organizational goals